Error Performance of Joint Transmit and Receive Antenna Selection in Two Hop Amplify-and-Forward Relay System over Nakagami-m Fading Channels - Yilmaz, Ahmet; Kucur, Oğuz (IEEE, 2010)
In this paper, performance of joint transmit and receive antenna selection in two hop amplify-and-forward relay system is analyzed over frequency non-selective and slowly Nakagami-m fading channels. In the system, all nodes are equipped with multiple antennas; Transmit Antenna Selection (TAS) is employed at the source and relay for transmission, Selection Combining (SC) is employed at the relay and destination for reception. The source and destination communicate by the help of single relay and source-destination link is not available. In this paper, we derive closed form Cumulative Distribution Function (CDF) and Moment Generating Function (MGF) of received Signal-to-Noise-Ratio (SNR). We also derive Symbol Error Probability (SEP) expressions for the considered system. Analytical results are validated by the simulations.
21st Annual IEEE International Symposium on Personal, Indoor and Mobile Radio Communications (PIMRC) -- SEP 26-30, 2010 -- Istanbul, TURKEY
Keywords: relayed transmission; joint transmit and receive antenna selection; Nakagami-m fading; MIMO